2023
DOI: 10.1155/2023/3400863
|View full text |Cite
|
Sign up to set email alerts
|

An Environmentally Friendly Compact Microfluidic Hydrodynamic Sequential Injection System Using Curcuma putii Maknoi & Jenjitt. Extract as a Natural Reagent for Colorimetric Determination of Total Iron in Water Samples

Abstract: The miniaturization of analytical systems and the utilization of nontoxic natural extract from plants play significant roles for green analytical chemistry methodology. In this work, the microfluidic hydrodynamic sequential injection (HSI) with the LED-phototransistor colorimetric detection system has been proposed to create an ecofriendly and low-cost miniaturized analytical system for online determination of iron in water samples using Curcuma putii Maknoi & Jenjitt. extracts as high stability and good s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The speciation of iron (Fe(II)/Fe(III)) is quite important in numerous fields such as plant science, the environment, pharmaceutics, and biology, and an interested reader can find several applications in the international literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. A screening of the recently published methods (2016 to date) revealed that the speciation of iron (and/or the determination of total iron) is based on more or less known red/ox pretreatment steps, followed by state-specific color-forming or fluorescent reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The speciation of iron (Fe(II)/Fe(III)) is quite important in numerous fields such as plant science, the environment, pharmaceutics, and biology, and an interested reader can find several applications in the international literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. A screening of the recently published methods (2016 to date) revealed that the speciation of iron (and/or the determination of total iron) is based on more or less known red/ox pretreatment steps, followed by state-specific color-forming or fluorescent reactions.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the principles of such procedures can be found in Table 1. As can be seen from the methods included in Table 1, they can be categorized into three main groups: (i) methods that are based on the reduction of Fe(III), typically by ascorbic acid or hydroxylamine [9,10,[12][13][14][15]17,19,20,24]; (ii) methods that are based on the oxidation of Fe(II) by H 2 O 2 [11,16,18]; and (iii) methods where both Fe(II) and Fe(III) interact with the selected probe, offering the possibility to perform total iron quantification in a single run (no speciation is reported though) [21][22][23]. Alternatively, a less-applied recent procedure is the column-based separation of Fe(II)/Fe(III) using cation exchange chromatography followed by compatible ICP detection [25].…”
Section: Introductionmentioning
confidence: 99%